Clinical outcomes after implantation of a new monofocal intraocular lens with enhanced intermediate function in patients with preperimetric glaucoma - Chung, Ho Seok; Jang, Joon Hyuck; Lee, Hun; Kim, Jae Yong; Tchah, Hungwon (Frontiers in Medicine, 2024)
Purpose We evaluated the clinical outcomes after implantation of a new monofocal intraocular lens (IOL) with enhanced intermediate function in patients with preperimetric glaucoma and compared those with patients without retinal nerve fiber layer (RNFL) defects. Methods All patients were implanted bilaterally a new monofocal IOL with enhanced intermediate function. Patients with bilateral RNFL defects and no glaucomatous visual field defects were classified as the preperimetric glaucoma group. A total of 60 eyes of 30 patients with preperimetric glaucoma were compared with 60 eyes of 30 patients without RNFL defects. Uncorrected distance visual acuity (UDVA), uncorrected intermediate visual acuity (UIVA), uncorrected near visual acuity (UNVA), defocus curve, contrast sensitivity, and questionnaire were evaluated 1 month and 3 months after surgery. Results No difference in binocular UDVA, UIVA, and UNVA was evident between the two groups at 1 and 3 months postoperatively. Additionally, there were no significant differences between the two groups regarding the proportion of severe or very severe photic phenomena, such as glare and halos, or the overall satisfaction. Conclusion Bilateral implantation of a new monofocal IOL with enhanced intermediate function in patients with preperimetric glaucoma demonstrated commensurate clinical outcomes and could be considered a feasible alternative.